The effect of next day responsibilities and an adaptive purchase task on cannabis demand. (1st October 2021) - Ferguson, Erin; Bush, Nicholas; Yurasek, Ali; Boissoneault, Jeff
Highlights: Original and adaptive marijuana purchase tasks (MPT) measured cannabis demand. An adaptive MPT allowed for selection of participants' preferred cannabis product. Adaptive marijuana purchase task indices correlated with cannabis use variables. Cannabis demand was sensitive to next-day work responsibilities. Responsibility-related decreases in demand were greater on adaptive vs. original MPT. Abstract: Background: The marijuana purchase task (MPT) is a commonly used behavioral economic measure of relative cannabis value (i.e. demand) that presents specific methodological concerns due to non-standardized measurement, variability in modality of use, and evolving legalization policies. Refinement of the task is critical to improve task ecological validity and accurate measurement of cannabis demand. The present study examined the construct validity of an adaptive MPT that allowed for participant selection of their preferred cannabis-based product and unit of measurement and the effect of next-day responsibilities on demand. Methods: Participants reporting at least monthly cannabis use (N = 186, 40.3 % women, Mage = 33.59) were recruited via Amazon Mechanical Turk and completed the original MPT and our adaptive form with 2 next-day responsibilities scenarios (no responsibilities vs. morning job interview) for each MPT. Cannabis use motives, problems, and risk for cannabis use disorder were also assessed. Results: Cannabis demand was sensitive to next-day responsibility, with higher hypothetical consumption observed in the no responsibilities condition. Responsibility-related decreases in Omax (F(1, 185) = 4.83, p = .029, η 2 p = .03) were significantly greater on the adaptive MPT than the original MPT. Demand indices derived from the adaptive MPT were significantly correlated with cannabis problems (rbreakpoint = .19, rPmax = 0.18, relasticity =-0.18) and motives (rrange =-.32−.25), and demand metrics from the original MPT. Conclusions: Results provide preliminary support for the construct validity of an adaptive MPT and suggest that early-morning work responsibilities may reduce cannabis demand. Continued research is needed to further refine this task and determine implications for cannabis use disorder intervention and prevention approaches.